Video marketing strategy : harness the power of online video to drive brand growth - Mowat, Jon, ....- (London ; : Kogan Page, 2018)
Video is the single most effective tool that marketers have to raise brand awareness, increase sales, drive website traffic and deliver ROI on marketing budgets. Driven by consumer demand and with the backing of the largest social media platforms, our world is becoming 'video first'. Video Marketing Strategy allows marketers to harness the power of video and create effective video campaigns. This in-depth look at the world's most powerful medium helps brands to radically magnify their voice by tapping into a level of emotional engagement that can't be achieved any other way. The book explores both theory (why are humans so affected by video on mobile devices?) and practice (what's the key to making videos that deliver results?).It looks at how multiple videos form wider campaigns and covers content hubs, activation strategies and testing. It is filled with invaluable advice, tips and strategies for incorporating video into a wider content marketing plan. Written by an award-winning video marketer with decades of experience, Video Marketing Strategy gives readers the magic formula to create engaging, effective content. Truly global in scope, it features case studies from around the world, and shows how marketers from all sectors and industries have used video campaigns successfully. Featuring insights from prominent industry practitioners Video Marketing Strategy is jam-packed with guidance on how to make videos that cut through the market place and deliver measurable results.
Includes bibliographical references and index.
Keywords: Internet marketing; Internet videos; Video marketing